Comparison of scattering phase functions of reacting and non-reacting pulverised fuel particles. (1st March 2021) - Koch, M.; Pörtner, L.; Gu, Y.; Schiemann, M.; Rohlfs, W.; Kneer, R.
Highlights: New setup for measuring phase function on single particles and particle streaks. Investigation of cold and burning coal particles. Imaginary and real part of IOR inversely calculated utilizing Mie theory. For cold coal particles: Re(IOR) = 1.4 and Im(IOR) = 0.1. Low sensitivity of phase function wrt Im(IOR) complicates its determination. Abstract: This study investigates the scattering properties of cold and reacting (burning) particles with focus on the experimental quantification of the complex index of refraction (IOR). The scattering phase function for Colombian bituminous coal is measured experimentally using two different setups and the IOR is determined from these data using an inverse approach. The first experimental setup is designed for single cold fuel particle characterization, with the particle being spatially fixed contactless using an acoustic levitator. In the second setup, the scattering properties of particle streaks, provided by a flat flame burner, are measured, allowing also for reacting particles to be investigated. In both setups, a broadband light source irradiates the single particle/particle streak and the scattered radiation is quantified by a spectrometer placed at altering angular positions. Reacting particles are studied in an oxy-fuel atmosphere. For both setups, Mie theory is used for modelling the optical particle properties.